Hematological parameters in children with Down syndrome - Renato Nisihara; Alana S. C. Souza; Letícia R. Finatti; Nancy O. Palmieri (Sociedade Brasileira de Patologia Clínica, 2015)
Introduction: There are few studies that investigated whether Down syndrome (DS) interferes with references values for complete blood counts (CBC) test in children with the syndrome. Objective: This study aimed to analyze the results of CBC performed in children with DS. Patients and methods: Data from CBC of DS children were included; at the time of examination they were aged between 2 and 10 years and had no clinical signs and/or symptoms of infectious disease. The hematological parameters analyzed were: total number of erythrocytes (RBC), hemoglobin (Hb) concentration, hematological indices, platelet count, and total number of leucocytes. Additionally, we compared the collected parameters according to gender and age of the children studied. Results: A total of 203 CBC (100 girls and 103 boys) were evaluated. In general, no significant differences were observed in studied parameters between the values found in samples of DS children and the values described in the literature as a reference for children in this age group. No difference in the prevalence of anemia was observed in relation to gender (p = 0.33), 14/103 (13.6%) boys, and 11/100 (11%) girls had anemia. However, the Hb and hematological indices values found in boys was significantly lower than in girls (p < 0.001). Conclusion: This investigation is the first one in Brazil to present and analyze the CBC results of DS children, reporting that their hematological indices are within the expected range for children without DS. Additionally, it was found that 12.3% of them had anemia.